2017
DOI: 10.1186/s40348-016-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Renal consequences of preterm birth

Abstract: BackgroundThe developmental origin of health and disease concept identifies the brain, cardiovascular, liver, and kidney systems as targets of fetal adverse programming with adult consequences. As the limits of viability in premature infants have been pushed to lower gestational ages, the long-term impact of prematurity on kidneys still remains a significant burden during hospital stay and beyond.ObjectivesThe purpose of this study is to summarize available evidence, mechanisms, and short- and long-term renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 73 publications
5
99
0
4
Order By: Relevance
“…167,168,124 F I G U R E 2 Role of mast cells for reproductive processes. [186][187][188] However, there is a recent study reporting opposite results as a significant lower number of MCs in the decidua of patients suffering from preterm birth was observed when compared to samples obtained from term births. A well-balanced physiological number and activation of uMCs is important for reproductive processes including ovulation, implantation, tissue remodeling, decidualization, spiral artery remodeling, placentation, fetal development, and uterus contractions that are in turn relevant for giving birth.…”
Section: Role Of Umcs For Ovulationmentioning
confidence: 96%
See 1 more Smart Citation
“…167,168,124 F I G U R E 2 Role of mast cells for reproductive processes. [186][187][188] However, there is a recent study reporting opposite results as a significant lower number of MCs in the decidua of patients suffering from preterm birth was observed when compared to samples obtained from term births. A well-balanced physiological number and activation of uMCs is important for reproductive processes including ovulation, implantation, tissue remodeling, decidualization, spiral artery remodeling, placentation, fetal development, and uterus contractions that are in turn relevant for giving birth.…”
Section: Role Of Umcs For Ovulationmentioning
confidence: 96%
“…185,126 Preterm delivery is a global health problem that is associated with high incidence of perinatal and neonatal death and with short-and long-term health consequences later in life. [186][187][188] However, there is a recent study reporting opposite results as a significant lower number of MCs in the decidua of patients suffering from preterm birth was observed when compared to samples obtained from term births. 189 The exact understanding of the role of MCs in processes underlying initiation and maintaining of pregnancy as well as induction of birth are important to prevent pregnancy pathologies on the one hand and for the development of effective treatment options on the other hand and need to be focused on future research.…”
Section: Influence Of Umcs On Implantation and Tissue Remodeling Dumentioning
confidence: 96%
“…All these conditions may induce renal hypoperfusion and hypoxia [7-9]. As focused on in very recent reviews, not only the assessment of renal function is often limited and difficult in preterm infants [5, 10], but additionally, kidney hypoperfusion preceding renal dysfunction may be subclinical [11]. So, research of early markers of both renal injury and hypoperfusion is advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the excretion extent of CFQ correlated with glomerular filtration rate in dogs; however, data in calves are not available (Taverne, van Geijlswijk, Heederik, Wagenaar, & Mouton, 2016). The rapid elimination of the drug in premature calves could be due to increased cardiac output, which would lead to an increase in glomerular filtration rate (Stritzke, Thomas, Amin, Fusch, & Lodha, 2017). These cardiovascular changes F I G U R E 2 Semi-logarithmic plasma concentration-time curves of ceftriaxone following intravenous (IV) and intramuscular (IM) administrations at a dose of 20 mg/kg in premature calves (n = 6, mean ± SD) may be caused due to hypoxia associated with premature birth (Aydogdu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%